Meningkatkan Keaktifan Anak Autis Dalam Mengikuti Kegiatan Melalui Terapi Behavioral Di Wisma Halimun - Lorentius Goa (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2021)
The term autism comes from the word “ auto” which means “ yourself ” while ” ism ” means “ a stream “if you join it means that an understanding is interested in myself. So, autism is a child who is interested in his world / aloof. The factor that causes autism 8 – 11 % of children with are genetic, but it is also caused by genetics and viruses. Behaviourism is a scientific view of human behaviour. It is orderly behaviour and carefully controlled experiments will reveal the laws that control behaviour. Every individual has the same positive and negative tendencies. The behavioristic theory is a theory that applies the principle of strengthening stimulus and response. This study aims to describe the three less active children participating in behaviour therapy activities at the Halimun Paulus underworld. This study used a quantitative experimental research design. Based on the results of the study with the methods used by pretest and posttest design for 5 subsidiaries of children’s activeness, the following results are obtained: the first subject AF from the pretest got a score of 56,6 and the posttest got a value of 72,2, then an increase of 15,6. And the second subject FG from the pre-test got a value of 52, and the post-test got a value of 65, then it has increased in value by 13. While the third subject of the KF from the pre-test received a value of 53,2, and the test post received a value of 68,2, a 15 increase. So seen from the three subjects which experienced the highest increase in AF 15,6 and second-order KF had an increase of 15, and the third had an increase of 13.